A Standardized Approach for Category II Fetal Heart Rate with Significant Decelerations: Maternal and Neonatal Outcomes - Shields, Laurence E.; Wiesner, Suzanne; Klein, Catherine; Pelletreau, Barbara; Hedriana, Herman L. (American Journal of Perinatology, 2018)
Objective To determine if a standardized intervention process for Category II fetal heart rates (FHRs) with significant decels (SigDecels) would improve neonatal outcome and to determine the impact on mode of delivery rates.Study Design Patients with Category II FHRs from six hospitals were prospectively managed using a standardized approach based on the presence of recurrent SigDecels. Maternal and neonatal outcomes were compared between pre- (6 months) and post-(11 months) implementation. Neonatal outcomes were: 5-minute APGAR scores of <7, <5, <3, and severe unexpected newborn complications (UNC). Maternal outcomes included primary cesarean and operative vaginal birth rates of eligible deliveries.Results Post implementation there were 8,515 eligible deliveries, 3,799 (44.6%) were screened, and 361 (9.5%) met criteria for recurrent SigDecels. Compliance with the algorithm was 97.8%. The algorithm recommended delivery in 68.0% of cases. Relative to pre-implementation, 5-minute APGAR score of <7 were reduced by 24.6% (p < 0.05) and severe UNC by −26.6%, p = < .05. The rate of primary cesarean decreased (19.8 vs 18.3%, p < 0.05), while there were nonsignificant increases in vaginal (74.6 vs 75.8%, p = 0.13) and operative vaginal births (5.7 vs 5.9%, p = 0.6).Conclusion Standardized management of recurrent SigDecels reduced the rate of 5-minute APGAR scores of < 7 and severe UNC.
Keywords: fetal heart rate; Category II; neonatal outcome; cesarean birth